Zirconium carbide nanofiber aerogel and preparation method thereof
The preparation of zirconium carbide nanofiber aerogels through electrospinning technology has solved the problem of insufficient performance of zirconium carbide nanowire aerogels in the prior art, and achieved efficient preparation of zirconium carbide nanofiber aerogels with excellent heat insulation, compressive resistance and tensile strength.
Patent Information
- Application Number
- CN202411964290.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
It is difficult to prepare zirconium carbide nanowire aerogels with excellent thermal insulation properties, compressive resistance and tensile strength in the prior art, and the zirconium carbide products prepared by traditional methods are high in density, making it difficult to achieve lightweight and high weather resistance requirements.
Through electrospinning technology, zirconium source, starch, water and spinning additives are mixed uniformly to form a spinning liquid, zirconium carbide nanofiber aerogel blank is prepared, and zirconium carbide nanofiber aerogel is formed through calcination process.
The prepared zirconium carbide nanofiber aerogel has excellent nanofiber length, small aerogel pore size, excellent thermal insulation, compressive resistance and tensile strength, and meets the requirements of lightweighting and high weather resistance in ultra-high temperature extreme environments.
Smart Images

Figure CN119877150A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aerogels, and in particular relates to a zirconium carbide nanofiber aerogel and a preparation method thereof. Background Art
[0002] The latest research found that zirconium carbide (ZrC) has the advantages of high melting point, excellent thermal stability and chemical stability, and better ablation resistance than borides. It can be used in ultra-high temperature extreme environments above 2000°C, and it has a relatively low density among ultra-high temperature ceramics, making it the most promising candidate material in the aviation and aerospace fields. Therefore, zirconium carbide (ZrC) materials are increasingly becoming a hot topic in the field of materials research at home and abroad.
[0003] Traditional zirconium carbide is mainly in powder form. This is because zirconium carbide prepared by traditional methods has poor filamentary properties and is difficult to produce into filamentary zirconium carbide. Powdered zirconium carbide mostly has a small specific surface area, and the zirconium carbide products prepared therefrom have high density and poor thermal insulation, making it difficult to achieve the requirements for lightweight and high weather resistance of the prepared products.
[0004] In order to improve the performance of zirconium carbide, researchers in this field have tried to prepare zirconium carbide in the form of aerogel. A document discloses a method for preparing zirconium carbide nanowire aerogel, which includes: first preparing a zirconium carbide precursor solution; placing the zirconium carbide precursor solution in a mold, and after freezing, vacuum drying to obtain a porous zirconium carbide precursor; heating and keeping the porous zirconium carbide precursor in an inert gas atmosphere to obtain a zirconium carbide nanowire aerogel. Although zirconium carbide nanowire aerogel has been prepared, the nanowires in the aerogel are short and the cross-connection between the nanowires in the aerogel is poor, which results in relatively poor thermal insulation, compressive resistance, and tensile strength of the zirconium carbide nanowire aerogel, which in turn affects the quality of the next process product. Summary of the invention
[0005] The main purpose of the present invention is to provide a zirconium carbide nanofiber aerogel and a preparation method thereof. The technical problem to be solved is how to provide a preparation method of zirconium carbide nanofiber aerogel so that it can be made into a zirconium carbide nanofiber aerogel blank by electrostatic spinning, and the blank can be further calcined to form a zirconium carbide nanofiber aerogel with good nanofiber length.
[0006] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. According to a method for preparing zirconium carbide nanofiber aerogel proposed in the present invention, the method comprises the following steps:
[0007] The zirconium source, the carbon source, water and the spinning aid are mixed evenly to form a spinning solution; the carbon source is starch;
[0008] The spinning solution is electrospinned to prepare a zirconium carbide nanofiber aerogel blank;
[0009] The zirconium carbide nanofiber aerogel blank is calcined to obtain the zirconium carbide nanofiber aerogel.
[0010] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0011] Preferably, in the aforementioned preparation method, the starch is potato starch.
[0012] Preferably, in the aforementioned preparation method, the zirconium source is selected from at least one of zirconium acetate, zirconium n-propoxide and zirconyl chloride octahydrate; and the spinning aid is selected from at least one of polyvinyl pyrrolidone, polyacrylonitrile and polyvinyl alcohol.
[0013] Preferably, in the aforementioned preparation method, the mass ratio of the zirconium source to the carbon source in the spinning solution is 2 to 1:1.
[0014] Preferably, in the aforementioned preparation method, the spinning solution comprises, by mass percentage, 30-50% of a zirconium source, 20-35% of a carbon source, 1-10% of a spinning aid, and 20-30% of water.
[0015] Preferably, in the aforementioned preparation method, the electrospinning comprises: the propulsion speed of the spinning solution is 0.12 to 1 mL / h, the spinning voltage is 20 to 30 KV, and the distance from the spinning needle to the receiving screen is 10 to 20 cm.
[0016] Preferably, in the aforementioned preparation method, the calcination comprises:
[0017] The zirconium carbide nanofiber aerogel blank is placed in a vacuum system and kept at a first temperature of 500-800° C. for 1-4 hours; then the temperature is continuously raised to a second temperature of 1100-1500° C. and kept at this temperature for 1-3 hours.
[0018] Preferably, in the aforementioned preparation method, the heating rate of the first temperature is 1 to 10°C / min, and the heating rate of the second temperature is 5 to 20°C / min.
[0019] The purpose of the present invention and the technical problems solved therein are also achieved by adopting the following technical solutions: According to the zirconium carbide nanofiber aerogel proposed by the present invention, the carbon source raw material of the aerogel is starch.
[0020] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0021] Preferably, the aforementioned aerogel, wherein the aerogel is prepared by the aforementioned scheme, the length of the nanofibers in the aerogel is greater than 10 cm; the specific surface area of the aerogel is greater than 12 m 2 / g; the average pore size of the aerogel is less than 30nm.
[0022] By means of the above technical solution, the zirconium carbide nanofiber aerogel and the preparation method thereof proposed in the present invention have at least the following advantages:
[0023] 1. The present invention provides a zirconium carbide nanofiber aerogel and a preparation method thereof. The readily available, non-toxic and inexpensive starch is used as a carbon source, which is mixed with a zirconium source, water and a spinning aid to form a spinning solution. The zirconium carbide nanofiber aerogel blank can be prepared by an electrostatic spinning process. The blank is calcined to prepare the zirconium carbide nanofiber aerogel. The zirconium carbide nanofiber aerogel prepared by the present invention has excellent nanofiber length, and the aerogel pore size formed by the interweaving of nanofibers inside the aerogel is small. The aerogel has excellent thermal insulation performance, compressive resistance and tensile strength.
[0024] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a process flow chart of preparing zirconium carbide fiber aerogel according to various embodiments of the present invention;
[0026] Figure 2 This is the SEM image of the zirconium carbide nanofiber aerogel obtained in Example 1 (magnification 500);
[0027] Figure 3 This is the SEM image of the zirconium carbide nanofiber aerogel obtained in Example 1 (magnification 20000);
[0028] Figure 4 This is the SEM image of the zirconium carbide nanofiber aerogel obtained in Example 2 (magnification 20000);
[0029] Figure 5 This is the SEM image of the zirconium carbide fiber aerogel obtained in Example 8 (magnification 100). DETAILED DESCRIPTION
[0030] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a zirconium carbide nanofiber aerogel and its preparation method proposed by the present invention in combination with the accompanying drawings and preferred embodiments. Its specific implementation, structure, characteristics and effects are described in detail as follows.
[0031] The inventors found that the zirconium carbide preparation method disclosed in the prior art is difficult to produce nanocellulose blanks by electrospinning due to the difficulty in filament formation, and therefore it is difficult to produce zirconium carbide nanofiber aerogel. In addition, the preparation method disclosed in the prior art often uses organic matter as a carbon source, and a large amount of toxic gas will be generated during the preparation process, which is easy to cause pollution or damage to the environment and is not conducive to environmental protection.
[0032] Based on the above findings, the inventors tried to replace the carbon source with sugar carbon, prepare spinning solution, and obtain zirconium carbide nanofiber aerogel blanks through electrospinning treatment; the inventors also found in the research process that when disaccharides are used as the carbon source, although zirconium carbide aerogel can be prepared in the end, the fiber diameter in the prepared aerogel is relatively coarse and cannot meet the nano-level requirements. The inventors analyzed that the reason is that when disaccharides are used as the carbon source, during the calcination process of the zirconium carbide nanofiber aerogel blank, the disaccharides decompose too quickly to produce a large amount of water vapor, and the water vapor cannot be completely evaporated in time and will gather around the fibers. Furthermore, the water vapor gathered around the nanofiber aerogel blank affects the volatilization of the spinning aid in the blank, causing a large amount of volatile aids and water vapor to gather around the nanocellulose blank, resulting in adhesion and aggregation of the nanocellulose blank, so that the fiber diameter becomes coarse, thereby affecting the quality of the prepared aerogel. Furthermore, the inventors conducted in-depth research and found that a spinning solution prepared by mixing starch as a carbon source with a zirconium source, water, and a spinning aid can be used to prepare a zirconium carbide nanocellulose blank. When the blank is calcined, the starch is slowly decomposed by heat, and the water vapor formed can be evaporated and removed in time, which will not affect the volatilization and removal of the spinning aid in the nanocellulose blank. This avoids the problem of adhesion of moisture or spinning aids around the blank during the calcination process, and allows the spinning aids in the formed zirconium carbide nanofiber aerogel to be completely discharged. Therefore, the prepared zirconium carbide nanofiber aerogel has a small nanofiber diameter, excellent fiber length, good interweaving effect between fibers, and high purity, so that the zirconium carbide nanofiber aerogel of the present invention has excellent thermal insulation performance, compressive resistance and tensile strength.
[0033] Based on the above, the present invention provides a method for preparing zirconium carbide nanofiber aerogel, which comprises the following steps:
[0034] 1) Preparation of spinning solution.
[0035] The zirconium source, the carbon source, the water and the spinning aid are mixed evenly to form a spinning solution; the carbon source is starch. The present invention does not specifically limit the specific means of mixing the zirconium source, the carbon source, the water and the spinning aid to form the spinning solution, which can be achieved by conventional means such as stirring and ultrasound. For example, in some embodiments, the zirconium source, the carbon source, the water and the spinning aid are stirred at room temperature to mix them evenly to form a spinning solution. Preferably, in the aforementioned scheme, the carbon source is water-soluble starch; the water-soluble starch described in some embodiments includes: potato starch, sweet potato starch, mung bean starch, corn starch and wheat starch; in other embodiments, it is further preferred that the starch is potato starch; this is because potato starch has better binding properties with water, better solubility, is easier to spin, the content of spinning aid added to the spinning solution is small, and the carbonization rate of potato starch is also easy to control. During the calcination process of the zirconium carbide nanofiber aerogel blank, the moisture generated by starch carbonization and the large amount of volatile spinning aid are avoided from gathering around the blank, thereby avoiding the adhesion of the zirconium carbide nanocellulose blank, which is conducive to the preparation of zirconium carbide nanofiber aerogel with small fiber diameter, fine fiber and small pore size.
[0036] In order to obtain a stable spinning solution and ensure smooth spinning solution forming, the present invention further adopts the following measures:
[0037] The zirconium source used in some embodiments is selected from at least one of zirconium acetate, zirconium n-propoxide and zirconyl chloride octahydrate (ZrOCl2·8H2O); the spinning aid used in some embodiments is selected from at least one of polyvinyl pyrrolidone (PVP), polyacrylonitrile (PAN), and polyvinyl alcohol (PVA).
[0038] The above-mentioned technical solution, further, in order to ensure the purity of the nanofibers in the zirconium carbide nanofiber aerogel, ensure the excellent performance of the nanofibers, and reduce the fiber breakage inside the aerogel, in some embodiments, the mass ratio of the zirconium source to the carbon source is strictly controlled to be 2 to 1: 1. If the ratio of the zirconium source to the carbon source is too large, it may not be possible to prepare zirconium carbide with a sufficiently high purity, and a large amount of zirconium oxide will exist in the zirconium carbide nanofiber aerogel, so that the prepared zirconium carbide nanofiber aerogel has defects in temperature resistance and heat insulation, thereby affecting the temperature resistance and heat insulation performance of the product; if the ratio of the zirconium source to the carbon source is too small, the length of the nanofibers in the prepared zirconium carbide nanofiber aerogel is relatively small, which may cause the various properties of the aerogel (such as heat insulation performance, pressure resistance, etc.) to be affected, and the product quality is poor.
[0039] The above scheme, further, in order to make the zirconium carbide nanofibers prepared by the present invention have good filament forming performance, small nanofiber diameter and good fiber length; the present invention further limits the content of each component in the spinning solution, specifically as follows:
[0040] Calculated by mass percentage, 30-50% zirconium source, 20-35% carbon source, 1-10% spinning aid, and 20-30% water.
[0041] In the above scheme, if there is too much zirconium source in the spinning solution, more zirconium oxide will appear in the prepared zirconium carbide nanofiber aerogel, which will affect the length of nanofibers in the prepared aerogel, and even affect the thermal insulation performance and other performance indicators of the prepared product. Furthermore, if the content of spinning aid in the spinning solution is too little, the spinning solution is difficult to form, and then it is difficult to make the spinning solution into a zirconium carbide nanofiber aerogel blank by electrostatic spinning; if the content of spinning aid in the spinning solution is too high, on the one hand, it is difficult to prepare nanofiber filaments, and on the other hand, even if the prepared zirconium carbide nanofiber aerogel is prepared, the diameter of the nanofibers it contains will be significantly increased, and even affect the pore size of the aerogel, thereby affecting the thermal insulation performance and other properties of the zirconium carbide nanofiber aerogel.
[0042] Preferably, in some other embodiments, the mass ratio of the zirconium source to the carbon source in the spinning solution is 2-1.5:1; and in terms of mass percentage, the content of each component of the spinning solution is 35-50% zirconium source, 23-33% carbon source, 1-10% spinning aid, and 20-30% water. The zirconium carbide nanofiber aerogel obtained under this condition has good nanofiber filamentation performance and excellent various properties of the aerogel.
[0043] 2) The spinning solution prepared in the above scheme is made into a zirconium carbide nanofiber aerogel blank by electrospinning. The process includes the following steps or process operations:
[0044] In some embodiments, in the electrospinning operation, the propulsion speed of the spinning solution is 0.12-1 mL / h, the spinning voltage is 20-30 KV, and the distance from the spinning needle to the receiving screen is 10-20 cm. There is no specific limitation on the material of the receiving screen for electrospinning. In some embodiments, aluminum foil and PET are used. The present invention limits the propulsion speed, voltage and distance from the spinning needle to the receiving screen of the spinning solution, and the prepared zirconium carbide nanofiber aerogel has a long fiber length and a small fiber diameter, and significantly improves the production efficiency. If the propulsion speed is too slow, the voltage is too high, and the distance from the spinning needle to the receiving screen is smaller, although nanofibers with smaller diameters can be formed, the product production efficiency is significantly reduced or the production cost is increased. If the propulsion speed is too fast, the voltage is too low, and the distance from the spinning needle to the receiving screen is larger, the nanofiber diameter in the prepared zirconium carbide nanofiber aerogel is thicker, and the density of the aerogel is increased, which is not conducive to making the further processed products thinner and lighter, and the fiber diameter is thicker.
[0045] 3) calcining the zirconium carbide nanofiber aerogel blank to obtain the zirconium carbide nanofiber aerogel material.
[0046] First temperature calcination: Place the zirconium carbide nanofiber aerogel blank in a vacuum system, heat it to 500-800°C at a heating rate of 1-10°C / min, and keep it warm for 1-4 hours. Under this condition, the carbon source is carbonized under high temperature, the zirconium source forms zirconium oxide under high temperature, and the spinning aid in the zirconium carbide nanofiber aerogel blank is calcined and removed. In the above scheme, if the heating rate is too fast or the insulation temperature is too high, the purity of the prepared product will be reduced.
[0047] Second temperature calcination: After the first temperature insulation is completed, the temperature is raised to at least 1100°C at a heating rate of 5-20°C / min on the basis of the first temperature. Preferably, in some embodiments, the temperature is raised to 1100-1500°C, kept for 1-3 hours, and then cooled to room temperature to obtain zirconium carbide nanofiber aerogel. Under this temperature condition, the zirconium source and the carbon source can react to form zirconium carbide, and the temperature is relatively low, which is conducive to saving energy costs.
[0048] The above scheme of the present invention proposes a new preparation process of zirconium carbide nanofiber aerogel, which fills the process gap of preparing zirconium carbide nanofiber membrane aerogel by spinning process, and the zirconium carbide nanofiber aerogel prepared by this process has excellent properties. In addition, sugar carbon is used as the carbon source, and no toxic gas is generated during the preparation process, which is beneficial to environmental protection.
[0049] The present invention also provides a zirconium carbide nanofiber aerogel, wherein the carbon source raw material of the aerogel is starch.
[0050] Furthermore, the zirconium carbide nanofiber aerogel prepared by the above scheme, wherein the nanofiber length in the aerogel is greater than 10 cm and the average pore size of the aerogel is less than 30 nm, can be used as a good ultra-high temperature heat-insulating material.
[0051] The zirconium carbide nanofiber aerogel described in the above scheme can be used in the fields of aviation, aerospace, thermal insulation materials, etc.
[0052] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0053] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0054] Example 1
[0055] This embodiment provides a zirconium carbide nanofiber aerogel and a preparation method thereof. The process flow chart of the following embodiment of the present invention is as follows: Figure 1 As shown, the details are as follows:
[0056] (1) Preparation of spinning solution: Potato starch, zirconium acetate, and spinning aid PVP are stirred evenly at room temperature to form a spinning solution. The contents of each component in the spinning solution are as follows: 45.3% zirconium acetate, 23.5% starch, 1.4% PVP, and 29.8% water, by mass percentage.
[0057] (2) The spinning solution is electrospinned to form a zirconium carbide nanofiber aerogel blank. The specific process is as follows:
[0058] The prepared spinning solution was sucked into the syringe of the electrospinning equipment, and the electrospinning parameters were set, including voltage of 30KV, injection speed of 0.12mL / h, and distance from the spinning needle to the receiving screen of 15cm. After setting the parameters, the spinning solution was prepared into a zirconium carbide nanofiber aerogel blank.
[0059] (3) calcining the fiber aerogel blank and then cooling it to room temperature to obtain the zirconium carbide nanofiber aerogel material. The specific process steps are as follows:
[0060] The zirconium carbide nanofiber aerogel blank was heated to 600°C at a rate of 5°C / min in a vacuum furnace and kept warm for 1 hour; further, the vacuum furnace was heated rapidly to 1500°C at a rate of 10°C / min and kept warm for 1 hour; after the insulation was completed, the temperature was cooled to room temperature to obtain the zirconium carbide nanofiber aerogel material.
[0061] Performance Testing
[0062] The fiber diameter, pore size, thermal insulation, thermal conductivity, compressive strength, and tensile strength of the zirconium carbide nanofiber aerogel prepared in this embodiment were tested as follows:
[0063] Fiber diameter detection: Use scanning electron microscopy to observe the morphology of aerogel and measure the diameter of nanofibers;
[0064] Fiber length detection: Use scanning electron microscopy to observe the morphology of aerogel and measure the length of nanofibers;
[0065] Aerogel pore size and specific surface area detection: Use BET specific surface area tester to test its pore size and specific surface area;
[0066] Thermal insulation test: Use a flat furnace to set the hot surface temperature to 1000℃ and measure the cold surface temperature of a sample with a thickness of 1mm;
[0067] Thermal insulation coefficient detection: Use laser thermal conductivity tester to test;
[0068] Compression and tensile strength testing: Use electronic universal testing machine for testing.
[0069] result
[0070] The electron microscope scanning results of the zirconium carbide nanofiber aerogel prepared in this example are shown in Figure 2 and Figure 3 The test results of other indicators are shown in Table 1.
[0071] Example 2
[0072] This embodiment provides a zirconium carbide nanofiber aerogel and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, except that:
[0073] (1) Preparation of spinning solution: The contents of the components in the spinning solution, by mass percentage, are: 43.2% zirconium acetate, 26.3% potato starch, 2.1% PVP, and 28.4% water.
[0074] (2) In the process of preparing the zirconium carbide nanofiber aerogel blank by electrospinning the spinning solution, the distance from the spinning needle to the receiving screen is 20 cm.
[0075] The detection index and detection method are the same as those in Example 1.
[0076] The electron microscope scanning results of the aerogel prepared in this example are shown in Figure 4 The test results of other indicators are shown in Table 1.
[0077] Example 3
[0078] This embodiment provides a zirconium carbide nanofiber aerogel and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, except that:
[0079] (1) Preparation of spinning solution: The contents of the components in the spinning solution, by mass percentage, are: 43.2% zirconium n-propoxide, 26.3% potato starch, 2.1% PAN, and 28.4% water.
[0080] The detection index and detection method are the same as those in Example 1.
[0081] The test results of various indicators are shown in Table 1.
[0082] Example 4
[0083] This embodiment provides a zirconium carbide nanofiber aerogel and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, except that:
[0084] (1) Preparation of spinning solution: The contents of the components in the spinning solution, by mass percentage, are: 35.3% zirconium acetate, 32.2% potato starch, 9.5% PVP, and 23% water.
[0085] The detection index and detection method are the same as those in Example 1.
[0086] The test results of various indicators are shown in Table 1.
[0087] Example 5
[0088] This embodiment provides a zirconium carbide nanofiber aerogel and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, except that:
[0089] (1) During the electrospinning process, the electrospinning parameters were set as follows: voltage 20 KV, injection speed 0.5 mL / h, and the distance from the spinning needle to the receiving screen was 10 cm.
[0090] (2) During the calcination process, the zirconium carbide nanofiber aerogel blank was heated to 500°C at a rate of 1°C / min in a vacuum furnace and kept at that temperature for 2 hours; further, the temperature was further increased to 1500°C at a rate of 10°C / min and kept at that temperature for 1 hour.
[0091] The detection index and detection method are the same as those in Example 1.
[0092] The test results of various indicators are shown in Table 1.
[0093] Example 6
[0094] This embodiment provides a zirconium carbide nanofiber aerogel and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, except that:
[0095] (1) During the electrospinning process, the electrospinning parameters were set as follows: voltage 25 KV, injection speed 0.8 mL / h, and the distance from the spinning needle to the receiving screen was 13 cm.
[0096] (2) During the calcination process, the zirconium carbide nanofiber aerogel blank was heated to 800°C at a rate of 10°C / min in a vacuum furnace and kept at that temperature for 2.5 hours; further, the temperature was further increased to 1300°C at a rate of 5°C / min and kept at that temperature for 2 hours.
[0097] The detection index and detection method are the same as those in Example 1.
[0098] The test results of various indicators are shown in Table 1.
[0099] Example 7
[0100] This embodiment provides a zirconium carbide nanofiber aerogel and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, except that:
[0101] (1) Preparation of spinning solution: The contents of the components in the spinning solution are as follows, by mass percentage: 49% zirconium acetate, 30% potato starch, 1% PVP, and 20% water.
[0102] The detection index and detection method are the same as those in Example 1.
[0103] The test results of various indicators are shown in Table 1.
[0104] Example 8
[0105] This embodiment provides a zirconium carbide fiber aerogel and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, except that:
[0106] (1) Preparation of spinning solution: The contents of the components in the spinning solution, by mass percentage, are: 43.2% zirconium acetate, 26.3% sucrose, 2.1% PVP, and 28.4% water.
[0107] The detection index and detection method are the same as those in Example 1.
[0108] The electron microscope scanning results of the aerogel prepared in this example are shown in Figure 5 The test results of various indicators are shown in Table 1.
[0109] Example 9
[0110] This embodiment provides a zirconium carbide fiber aerogel and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, except that:
[0111] (1) Preparation of spinning solution: The contents of the components in the spinning solution, by mass percentage, are: 43.2% zirconium acetate, 26.3% corn starch, 2.1% PVP, and 28.4% water.
[0112] The detection index and detection method are the same as those in Example 1.
[0113] The test results of various indicators are shown in Table 1.
[0114] Table 1 Test results of various indicators in the embodiment
[0115]
[0116]
[0117] Note: “-” in the table means that it cannot be measured.
[0118] Combination Figures 2 to 5As shown in Table 1, the zirconium carbide nanofiber aerogel process provided by the present invention can be used to prepare zirconium carbide nanofiber aerogel, and the nanofibers in the zirconium carbide nanofiber aerogel are of excellent length and the nanofibers are rarely broken; the zirconium carbide nanofiber aerogel has good thermal insulation performance, strong compressive resistance, large specific surface area, and good tensile strength.
[0119] Comparing Example 8 with Examples 1-7, it can be seen that the fiber diameter of the zirconium carbide fiber aerogel prepared by using sucrose as the carbon source is significantly increased, and it cannot meet the nanofiber level requirements; in addition, during the experiment, the inventors also found that when using sucrose as the carbon source, a large number of bubbles are generated during the calcination process in the first temperature stage, causing the nanocellulose blanks to adhere and aggregate, and the prepared aerogel is as shown in the attached Figure 5 As shown, there are a large number of bubbles. The inventors speculate that this may be because sucrose decomposes too quickly during the calcination process, and its decomposition products form a large amount of water, which further causes the water and spinning aids in the nanocellulose blank to aggregate and condense, so that the spinning aids are difficult to remove completely and remain in the calcined products, which not only affects the diameter of the nanofibers, but also affects the various properties of the aerogel.
[0120] Comparing Example 9 with Example 1, it can be seen that the performance of the present invention using potato starch is better. The reasons are: potato starch has better binding properties with water, better solubility, is easier to spin, the content of spinning aid added to the spinning solution is small, the carbonization rate of potato starch is easier to control, and during the calcination process of the zirconium carbide nanocellulose blank, the moisture generated by the carbonization of the starch and the large amount of volatile spinning aid are avoided from aggregating, so as to avoid the adhesion of the zirconium carbide nanocellulose blank, thereby facilitating the preparation of zirconium carbide nanofiber aerogel with small fiber diameter, fine fiber and small pore size.
[0121] By comparing Examples 1, 2, 4 and 7, it can be seen that the preparation method of zirconium carbide nanofiber aerogel of the present invention is adopted, potato starch is used as the carbon source, the mass ratio of the zirconium source to the carbon source in the spinning solution is 2-1.5:1; and in terms of mass percentage, the content of each component of the spinning solution is 35-50% zirconium source, 23-33% carbon source, 1-10% spinning aid, and 20-30% water; the diameter of the zirconium carbide nanofiber aerogel nanofiber obtained under this condition is <130nm, the pore size of the aerogel is <20nm; the specific surface area is >13m 2 / g; thermal insulation coefficient is 0.03~0.05W·m -1 ·K -1 , the compressive strength is >5MPa, and the tensile strength is >1.9MPa. It can be seen that the zirconium carbide nanofiber aerogel obtained under this condition has good nanofiber filamentation performance and excellent performance of the aerogel.
[0122] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0123] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing zirconium carbide nanofiber aerogel, characterized in that: It includes the following steps: The zirconium source, the carbon source, water and the spinning aid are mixed evenly to form a spinning solution; the carbon source is starch; The spinning solution is electrospinned to prepare a zirconium carbide nanofiber aerogel blank; The zirconium carbide nanofiber aerogel blank is calcined to obtain the zirconium carbide nanofiber aerogel.
2. The preparation method according to claim 1, characterized in that: The starch is potato starch.
3. The preparation method according to claim 1, characterized in that: The zirconium source is selected from at least one of zirconium acetate, zirconium n-propoxide and zirconyl chloride octahydrate; the spinning aid is selected from at least one of polyvinyl pyrrolidone, polyacrylonitrile and polyvinyl alcohol.
4. The preparation method according to claims 1 to 3, characterized in that: The mass ratio of the zirconium source to the carbon source in the spinning solution is 2-1:
1.
5. The preparation method according to claim 4, characterized in that: The spinning solution comprises, by weight percentage, 30-50% of a zirconium source, 20-35% of a carbon source, 1-10% of a spinning aid, and 20-30% of water.
6. The preparation method according to claim 5, characterized in that: The electrostatic spinning comprises: the propulsion speed of the spinning solution is 0.12-1 mL / h, the spinning voltage is 20-30 KV, and the distance from the spinning needle to the receiving screen is 10-20 cm.
7. The preparation method according to claim 6, characterized in that: The calcination comprises: The zirconium carbide nanofiber aerogel blank is placed in a vacuum system and kept at a first temperature of 500-800° C. for 1-4 hours; then the temperature is continuously raised to a second temperature of 1100-1500° C. and kept at this temperature for 1-3 hours.
8. The preparation method according to claim 7, characterized in that: The heating rate of the first temperature is 1-10° C. / min, and the heating rate of the second temperature is 5-20° C. / min.
9. A zirconium carbide nanofiber aerogel, characterized in that: The carbon source raw material of the aerogel is starch.
10. The aerogel according to claim 9, characterized in that The aerogel is prepared by the preparation method according to any one of claims 1 to 8, wherein the length of the nanofibers in the aerogel is greater than 10 cm; the specific surface area of the aerogel is greater than 12 m 2 / g; the average pore size of the aerogel is less than 30nm.